예습 과제 활용 온라인 동영상 강의 수업 사례 연구: 대학교 토익 수업에서 - 조혜선; Cho Hyesun (Multimedia-Assisted Language Learning, 2020)
This study presents the teaching methods and post-survey results from two online courses utilizing recorded lectures and preview homework. The two courses, < TOEIC Reading 1 > and < TOEIC Listening 1 >, were taught at a university for a 15-week semester with a total of 107 enrolled students. The recorded lectures were uploaded on Google Classroom each week. Students were given preview homework before each lecture where they were required to study certain textbook pages and indicate the problem numbers where they had wrong answers on a given Google Form. The instructor then focused the lectures on where students’ weaknesses lie. At the end of the semester a survey was carried out asking students’ perception of online lectures, preview homework, attitude, and easiness of online LMS. The results reveal that students were overall satisfied with the online recorded lectures, showing positive responses on the effectiveness of reviewing preview homework in online lectures. The results show that adding the element of preview homework and feedback thereof to otherwise one-directional online lecture can help students engage and better understand the materials by focusing on what students feel difficult.